Characterization of Coding/Noncoding Variants for SHROOM3 in Patients with CKD - Prokop, Jeremy W; Yeo, Nan Cher; Ottmann, Christian; Chhetri, Surya B; Florus, Kacie L; Ross, Emily J; Sosonkina, Nadiya; Link, Brian A; Freedman, Barry I; Coppola, Candice J; McDermott-Roe, Chris; Leysen, Seppe; et al. (Journal of the American Society of Nephrology, 2018)
Interpreting genetic variants is one of the greatest challenges impeding analysis of rapidly increasing volumes of genomic data from patients. For example, is an associated risk gene for CKD, yet causative mechanism(s) of allele(s) are unknown. We used our analytic pipeline that integrates genetic, computational, biochemical, CRISPR/Cas9 editing, molecular, and physiologic data to characterize coding and noncoding variants to study the human risk locus for CKD. We identified a novel transcriptional start site, which results in a shorter isoform lacking the PDZ domain and is regulated by a common noncoding sequence variant associated with CKD (rs17319721, allele frequency: 0.35). This variant disrupted allele binding to the transcription factor TCF7L2 in podocyte cell nuclear extracts and altered transcription levels of in cultured cells, potentially through the loss of repressive looping between rs17319721 and the novel start site. Although common variant mechanisms are of high utility, sequencing is beginning to identify rare variants involved in disease; therefore, we used our biophysical tools to analyze an average of 112,849 individual human genome sequences for rare SHROOM3 missense variants, revealing 35 high-effect variants. The high-effect alleles include a coding variant (P1244L) previously associated with CKD ( =0.01, odds ratio=7.95; 95% CI, 1.53 to 41.46) that we find to be present in East Asian individuals at an allele frequency of 0.0027. We determined that P1244L attenuates the interaction of with 14-3-3, suggesting alterations to the Hippo pathway, a known mediator of CKD. These data demonstrate multiple new -dependent genetic/molecular mechanisms that likely affect CKD.